ARUS BARU LEMBAGA PENDIDIKAN ISLAM DI INDONESIA: DARI KUTTAB SAMPAI SEKOLAH ISLAM TERPADU - Ilham Muttaqi Hikam; Ken Zacky Azafran; Vivie Alifia Rachmah; Sutrimo Purnomo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic educational institutions in Indonesia have experienced significant developments with the emergence of various new ideological forms. The background to this research stems from the need to understand the dynamics of Islamic education reform, the emergence of integrated Islamic schools, contemporary Islamic educational ideologies, and the resurgent phenomenon of kuttab. The purpose of this research is to analyze the characteristics, ideological orientations, and social implications of these institutions for the national education system and Muslim society. The research method uses a qualitative approach through a literature review of several Islamic educational institutions. The results indicate that Islamic education reform has given rise to an integrative model that combines general and religious curricula. Integrated Islamic schools have become a symbol of modernization of education based on Islamic values. New ideologies emphasize the internalization of morals and the formation of a global Muslim identity. While the kuttab phenomenon reaffirms the importance of basic education based on the Quran. The implications of this research emphasize the need for educational policies that adapt to the diversity of Islamic ideologies, improve teacher quality, and develop a curriculum that balances spiritual needs and academic competencies. Recommendations are made for the need for open dialogue among stakeholders in Islamic education to maintain the relevance and sustainability of these ideological institutions in facing the challenges of the times.